A aprendizagem baseada em problemas (PBL): uma implementação na educação em engenharia na voz dos atores. - Ribeiro, Luis Roberto de Camargo (Universidade Federal de São Carlos, 2005)
Problem-based Learning or PBL, contrary to conventional instructional methods that place problems after concepts have been introduced, uses open-ended problems to initiate, focus and motivate the learning of theory. Besides favoring the construction of knowledge, this method proposes to contribute to the development of some nontechnical professional attributes deemed as important to the practice of engineering in a fast changing society. This work, an intervention-research design of a qualitative nature, sought to investigate an implementation of PBL in the teaching of engineering, the surrounding context and how it is assessed by the main actors: students and teacher. To this end the method was implemented in three administration theory courses offered in the undergraduate and graduate production engineering curricula and in the undergraduate civil engineering curriculum of a public university in São Carlos, SP, Brazil. The three courses covered similar syllabi and were taught by the same teacher. The data were collected by means of participant observation of classes and unstructured interviews with the teacher before, during and after the implementation and by way of an end-of-course questionnaire (with open questions) responded by the students, in which they were asked to opine on PBL, its advantages and disadvantages and its potential to meet the course goals. Additional data were collected at the University of Newcastle, Australia, by means of participant observation and unstructured interviews with some faculty. Grosso modo, the data collected prior to the implementation were analyzed in light of the literature on engineering education and higher education in general (Salum, Ramos, Sordi, Cunha, among others) and on the influence of institutional, cultural and individual aspects on the classroom (Zeichner, Dreeben, Lortie, Tardif, among others). The data collected during and after the implementation were analyzed vis a vis the literature on PBL especially the metaanalyses by Albanese & Mitchell, Vernon & Blake and Dochy et al., and the work of authors such as Barrows, Woods, Gijselaers, among others and Shulman s teacher knowledge base. The results showed that despite the differences among contexts the three classes reported the learning of the knowledge as well as the development of some skills and attitudes intended by the courses, in agreement with the teacher s assessment. The disadvantages indicated by the students and teacher are also similar, such as the need for more commitment and increased time. On the whole, the students reacted positively to PBL, which suggests the viability of its use in the contexts in question, provided that some aspects of the implementation are reconsidered and redimensioned. Besides, although it should not be taken as a substitute for teacher training, PBL showed to be an interesting tool in the teacher s professional development, especially concerning the improvement of the teacher knowledge base.
Keywords: Métodos de ensino; Ensino superior; Aprendizagem baseada em problemas; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO